Historia rozwoju doliny Warty w basenie uniejowskim - Petera-Zganiacz, Joanna; Forysiak, Jacek (Biuletyn Uniejowski, 2012)
The conditions existing in the Uniejów Basin were favourable to formation of outflow after successive glaciations due to subsidence in Adamow graben. The last glacial episode in this area was the Warta stage. During the recession of continental glacier the waters flew away towards the south, but when the glacier receded to the north, a valley began to form with an outflow in the northern direction. During the time of the Eemian Interglacial the valley bottom was fairly wide and it was on the ordinate of 80.0 m. above see level. In the Vistulian the aggradation tendencies dominated. A high Plenivistulian terrace formed in the Warta valley (but only in the southern part of the Uniejów Basin) and a low Late Plenivistulian terrace. On the surface of the vast low terraca there are remains of multichannel river system which formed in Younger Dryas and were reactivated in the Holocene. The Warta river-bed was gradually lowering from the begining of Holocene until the Atlantic period, when this tendency was reversed as a result of intensified humangenerated supply of mineral material into the river-bed. Over the last two centuries the Warta transformed into a one-channel river in consequence of strong human impact.